SUPRASEGMENTAL PHONEMICS IN ANAKALANG LANGUAGE IN CENTRAL SUMBA DISTRICT - Alex Djawa; Labu Djuli; Markus Sampe (Postgraduate School, Universitas Nusa Cendana, 2022)
In the Anakalang language, suprasegmental phonemics are found. Suprasegmental phonemics are found as in the word bada 'too', baďa 'animal', which is marked with a diacritic [']. aha 'wash' and baha 'wet', ali 'go home' and bali 'ball'. All pronunciations of the sound [ƀ] that are subjected to soft stress are phonetically marked with a small line above them. The pronunciation of the sound [ƀ] in the word aha 'wash is with a soft pressure, while the pronunciation of the sound [b] in the word baha is with a strong pressure. From the difference in pressure in the pronunciation, there is a difference in meaning. Likewise for the word bali. The sound [b] in the word bali is pronounced with a soft stress, while the [b] in the word bali 'bola' is pronounced with a strong stress which differentiates the meaning. The sound [b] is a voiced sound, but the sound [b] which is pronounced with soft pressure becomes a muted sound. Therefore, in this finding, apart from segmental phonemics, there are also suprasegmental phonemics. This finding shows that the Anakalang language is unique. It is called unique because suprasegmental phonemics are not found in Indonesian. Therefore, it is interesting to carry out further research with a broad dimension to obtain a complete and complete picture of the meaning of suprasegmental in this language.